Gottfried Benn and the Sublime Beauty of Cruelty - Párraga, Javier Martín (2019)
Gottfried Benn’s opus primum, Morgue und andere Gedichte was published in 1912 and it produced a radical change in contemporary German poetry. This paper offers an in-depth analysis of the whole book of poems, employing as a theoretical framework both the theories of those experts which contributed to the establishment of the concept of sublimity such as Addison, Burke or Dessoir as well as other poets who, like Benn himself, embraced a conception of sublimity which quite frequently made them renounce canonical formal beauty; which they replace by a certain eschatology which is both socially shocking and philosophically fertile.